2015
DOI: 10.1017/s175173111400322x
|View full text |Cite
|
Sign up to set email alerts
|

Response of growing ruminants to diet in warm climates: a meta-analysis

Abstract: The aim of this work was to establish the response of growing sheep, goats and cattle to different nutritional environments. Data from 590 publications representing 2225 treatments were analysed. The results showed that each 10% increase in NDF was accompanied by 0.11 g/kg live weight (LW) and 0.32 g/kg metabolic live weight (LW 0.75 ) decreases in DMI. Otherwise, the response of DMI to CP (CP%DM) content was curvilinear (P < 0.01), without any significant difference in the slope between species. The percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
2
8
0
1
Order By: Relevance
“…In cattle, much of the research investigating compensatory growth has pointed to food intake as one of the main factors leading to the occurrence of this phenomenon (Sainz et al, 1995). The results of Chapter 4 are in agreement with these previous reports and show a linear relationship between the ME intake and liveweight gain which is also agreement with more recent work on continuously growing cattle (Salah et al, 2015). Interestingly, this was independent of the type of restriction (ME or crude protein) and genotype of steers.…”
Section: Dry Matter Intakesupporting
confidence: 88%
“…In cattle, much of the research investigating compensatory growth has pointed to food intake as one of the main factors leading to the occurrence of this phenomenon (Sainz et al, 1995). The results of Chapter 4 are in agreement with these previous reports and show a linear relationship between the ME intake and liveweight gain which is also agreement with more recent work on continuously growing cattle (Salah et al, 2015). Interestingly, this was independent of the type of restriction (ME or crude protein) and genotype of steers.…”
Section: Dry Matter Intakesupporting
confidence: 88%
“…Retained N values for growing cattle offered various diets range from −9 to 89 g/day (Salah, Sauvant, & Archimède, ), and growing‐finishing beef cattle consuming grass silage‐based diets range from −6 to 101 g/day (Yan, Frost, Keady, Agnew, & Mayne, ). The quantities of N retained in the current study (47 g/day) were intermediate to those ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Under similar experimental conditions, Andrade and Pereira (1999) reported that DM intake decreased (p=0.09) when corn silage was replaced with sugarcane in Holstein heifer diets. Salah et al (2015) reported that DM intake and weight gain decreased significantly when dietary NDF concentration increased by 10%. Even though the inclusion of nitrogen-rich concentrates results in a significant increase in sugarcane intake by ruminants compared to supplementation with nonprotein nitrogen sources only (LASCANO et al, 2012), the formulation of high-energy diets for improved animal performance may not completely eliminate the inhibitory effect of sugarcane on DM intake.…”
Section: Discussionmentioning
confidence: 99%